Selective Autophagy Receptor p62/SQSTM1, a Pivotal Player in Stress and Aging - Kumar, Anita V.; Mills, Joslyn; Lapierre, Louis R. (Frontiers in Cell and Developmental Biology, 2022)
Efficient proteostasis is crucial for somatic maintenance and its decline during aging leads to cellular dysfunction and disease. Selective autophagy is a form of autophagy mediated by receptors that target specific cargoes for degradation and is an essential process to maintain proteostasis. The protein Sequestosome (p62/SQSTM1) is a classical selective autophagy receptor, but it also has roles in the ubiquitin-proteasome system, cellular metabolism, signaling, and apoptosis. p62 is best known for its role in clearing protein aggregates via aggrephagy, but it has recently emerged as a receptor for other forms of selective autophagy such as mitophagy and lipophagy. Notably, p62 has context-dependent impacts on organismal aging and turnover of p62 is usually concomitant with active proteostasis. In this review, we highlight recent advances in understanding the role of p62 in coordinating the ubiquitin-proteasome system and autophagy. We also discuss positive and negative effects of p62 on proteostatic outcome and its implications on aging and neurodegeneration. Finally, we relate the link between defective p62 and diseases of aging and examine the utility of targeting this multifaceted protein to achieve proteostatic benefits.